Efektivitas Pelayanan Perizinan Berusaha Di Mal Pelayanan Publik Karanganyar : Efektivitas Pelayanan Perizinan Berusaha Di Mal Pelayanan Publik Karanganyar - Khasanah, Lulu In; Haryanto, Aris Tri; Suranto, Joko (Solidaritas, 2023)
Abstrak The business licensing service is one of the various types of services available at the Karanganyar Public Service Mall under the responsibility of the Office of Capital Provision and One-Stop Integrated Services, Karanganyar Regency. The existence of business service licensing is intended so that the community can obtain legality for businesses that will be started or have already been carried out. This study aims to analyze the effectiveness of business licensing services at the Karanganyar Public Service Mall. Measuring effectiveness in this study uses 4 (four) indicators according to Fandy Tjiptono (2017: 200), namely (1) timeliness of service (2) Service accuracy (3) Politeness and ease of service (4) Ease of getting service. This study uses a descriptive, qualitative, and qualitative method. Data collection techniques; namely observation; and in-depth interviews. The informants in this study consisted of the Head of the Licensing Service for the Economy and People’s Welfare, Business Licensing Service Employees and service users at the Karanganyar Public Service Mall. Technique analysis data use the analysis steps are in accordance with the theory of Miles, Huberman and Saldana (2014: 14), namely: data condensation (data compaction), data presentation (data appearance), and drawing conclusions or verification (conclusion and verification). The results of this study indicate that the effectiveness of business licensing services at the Karanganyar Public Service Mall has been carried out effectively. However, there are still things that are felt to be less effective than the strict waiting time and shortage of staff at the Karanganyar Public Service Mall. Researchers suggest optimizing waiting times and regular technical guidance regarding OSS keywords : Effectiveness, Accuracy, Accuracy, Friendliness, Convenienc